A tumor-activatable particle with antimetastatic potential in breast cancer via inhibiting the autophagy-dependent disassembly of focal adhesion. (June 2018) - Wang, Yang; Yin, Sheng; Zhang, Li; Shi, Kairong; Tang, Jiajing; Zhang, Zhirong; He, Qin
Abstract: In attempts to explore the role of autophagy in breast cancer metastasis, we here report a tumor-activatable particle (named as "D/PSP@CQ/CaP") with the ability of efficient autophagy inhibition. D/PSP@CQ/CaP was prepared by coprecipitating chloroquine phosphate (CQ) with calcium chloride, in the form of chloroquine-calcium phosphate coprecipitate (CQ/CaP), onto the surface of a deep-tumor-penetrating doxorubicine (DOX)-loading core particle (named as "D/PSP"). CQ/CaP could partly disintegrate and release CQ within tumor microenvironment and totally be dissolved within lysosomes. Paxillin is a key component of focal adhesion which functions to anchor tumors cells within the primary tumor for limiting cancer cells' detachment from the primary tumor. We tested that autophagy inhibition caused by CQ released from CQ/CaP could reduce the degradation of paxillin by 2.9 folds in vitro and 2.5 folds in vivo ( vs. Control), respectively. Thus metastasis could be influenced by exploiting autophagy-dependent paxillin degradation. Data analysis together proved that D/PSP@CQ/CaP decreased the cancer metastatic extent by 7.5 folds ( vs. Control) on mice model via inhibiting the autophagy-dependent disassembly of focal adhesion. At the same time, the growth rate of tumors treated by D/PSP@CQ/CaP was inhibited by 9.1 folds ( vs. Control), which could be attributed to its effective tumor drug delivery. Graphical abstract: